Rewards and Cognitive Dissonance: The Impact of Cookie Policies in Information Ecosystems - Manuel Gabriel Vigariu; Constantin-Alexandru Marin (Journal of Research and Innovation for Sustainable Society)
In the digital age, where users' attention is an increasingly rare commodity, cookies have become an essential tool not only for optimizing online experiences, but also for the psychological manipulation of users. These small data files are used strategically to stimulate the brain's reward system as well as to avoid cognitive dissonance, a phenomenon that occurs when there is a conflict between users' expectations of the reality of their online interactions. By offering a personalized experience and constant rewards, the cookie policy helps to keep users connected in the digital space, preventing them from encountering dilemmas or unpleasant situations that could cause them to reconsider their commitment to the respective platforms